The righteous mind ebook Why good people are divided by politics and religion. - Haidt, Jonathan (2012)
NEW YORK TIMES BESTSELLER • The #1 bestselling author of The Anxious Generation and acclaimed social psychologist challenges conventional thinking about morality, politics, and religion in a way that speaks to conservatives and liberals alike—a “landmark contribution to humanity’s understanding of itself” ( The New York Times Book Review ). Drawing on his twenty-five years of groundbreaking research on moral psychology, Jonathan Haidt shows how moral judgments arise not from reason but from gut feelings. He shows why liberals, conservatives, and libertarians have such different intuitions about right and wrong, and he shows why each side is actually right about many of its central concerns. In this subtle yet accessible book, Haidt gives you the key to understanding the miracle of human cooperation, as well as the curse of our eternal divisions and conflicts. If you’re ready to trade in anger for understanding, read The Righteous Mind .